The burden and treatment of non-communicable diseases among healthcare workers in sub-Saharan Africa: a multi-country cross-sectional study - Müller, Sophie Alice; Elimian, Kelly; Rafamatanantsoa, Jean Florent; Reichert, Felix; Mosala, Francis; Böff, Lena; Touré, Sounan Fidèle; Boone, Idesbald; Ravaoarisoa, Lantonirina; Nduenga, Sagesse; Ortu, Giuseppina; Pozo-Martin, Francisco; et al. (Frontiers in Public Health, 2024)
Introduction: Noncommunicable diseases (NCDs), the leading cause of death globally, are estimated to overtake communicable diseases in sub-Sahara Africa, where healthcare workers (HCWs) play a crucial role in prevention and treatment, but are in extreme shortage, thereby increasing the burden of NCDs among this specific population. To provide evidence for policy-making, we assessed the NCD burden, associated factors and treatment among HCWs in four sub-Saharan African countries.We conducted a cross-sectional study across four sub-Saharan African countries (Côte d'Ivoire (CIV), Democratic Republic of the Congo (DRC), Madagascar (MDG), and Nigeria (NIG)) between February and December 2022. In a standardized questionnaire, sociodemographic, chronic disease and treatment data were self-reported. We estimated the prevalence of 1) at least one chronic disease, 2) hypertension, and used backward elimination logistic regression model to identify risk factors.We recruited a total of 6,848 HCWs. The prevalence of at least one chronic disease ranged between 9.7% in NIG and 20.6% in MDG, the prevalence of hypertension between 5.4% in CIV and 11.3% in MDG. At most, reported treatment rates reached 36.5%.The odds of each of both outcomes increased with age (at least one chronic disease adjusted odds ratio: